Multi‑objective Cooperative Control Strategy of Energy Storage Battery for Primary Frequency Regulation - ZHAO Xilin; CHEN Xiao (Taiyuan Ligong Daxue xuebao)
[Purposes] The integration of large-scale renewable energy into the power grid leads to the reduction of equivalent moment of inertia in the frequency control process and the shortage of standby capacity of traditional thermal power units for frequency modulation. The battery energy storage system (BESS) plays a good auxiliary role in solving these problems with its fast response and flexible regulation. However, the individual characteristics of BESS make it necessary to have a more refined control strategy when participating in power grid frequency regulation. [Methods] In this paper, the batteries were grouped according to the state of charge (SOC) to form energy storage units, and a system model of multiple energy storage units cooperating in primary frequency control was constructed; Then, the reasonable charging and discharging range of battery was determined by analyzing the relationship between the battery open-circuit voltage and the SOC in different environments, and the coordination strategy of each cell was designed according to the difference of SOC between battery cells, so as to realize the frequency regulation requirements while taking into account the battery operation safety; On this basis, the optimization problem was designed and solved to optimize the frequency regulation effect and the energy loss of the battery. [Results] The simulation results based on Matlab/Simulink show that the proposed control strategy can fully tap the potential of energy storage battery auxiliary frequency regulation and achieve a better balance between frequency regulation effect, energy storage loss, and depth of charge and discharge.